FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK WAJIB PAJAK ORANG PRIBADI YANG MELAKUKAN PEKERJAAN BEBAS - Wahyu Anggraeni, 08.05.52.0110; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2012)
This study aims to determine the factors that influence the illingness to pay taxes. Five variables:Awareness Paying Taxes, Knowledge and Understanding of Tax Regulation, PerceptionsÂ 0of the effectiveness of the tax system and used as predictors of service tax authorities that affect willingness to pay taxes.The study was conducted in Semarang Central LTO 2. The samples used as many as 100 individual taxpayers with free job. Questionnaire instrument used for data retrieval research. Multiple linear regression analysis techniques are used for hypothesis testing. The analysis Paying Taxes awareness is also a positive influence on willingness to pay taxes. Knowledge and Understanding of Tax Rules taxpayer positive influence on willingness to pay taxes. Perception of the effectiveness of the tax system is also a positive influence on willingness to pay taxes and service tax authorities have a positive influence on willingness to pay taxes.Keywords: Awareness of tax paying, knowledge andÂ nderstanding, the effectiveness of the tax system, tax authorities will pay the service tax.